Aprendamos sobre el mercado de nuestra comunidad - Guevara Alvarado, Jhoiver (2020)
Currently our peoples bring with them a series of limitations regarding the development of skills, values, attitudes, abilities and competencies; which do not let us move forward as a person and as a country full of opportunities. One of which Peruvians have a great deficit in producing the necessary tools to have our own companies and factories of various products to be exported to other countries._x000D_ It is because of the aforementioned that in this learning strategy called “let's learn about the market” this topic has been touched upon because many of the students of all levels and ages are unaware of the supply and demand, goods and services. Well, this work is also detailed about the relationship of the person and society to generate a vision and mission to the point that we want to reach both individually and collectively (country). In such a way that in the theoretical framework, characters such as: Minedu, Dongil and Cano, Candiotti, Hojholt, Bonet, Nuñez, Mayo and others have been cited._x000D_ On the other hand, this work is based on pedagogues who give us a range of orientations on how the educational process should be developed with children of all levels and educational cycles, within which we cite Minedu, Gálvez, García, Ausubel, Brunner, among others that is recorded in the bibliography.